Pengaruh Penambahan Puree Wortel (Daucus Carota L.) Terhadap Karakteristik Manisan Paladang - Andriani, Asri; Suparthana, Putu; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Candied paladang is a dried candied fruit made from grated nutmeg and grated papaya shaped like balls. This research was aimed to determining the effect of carrot puree addition on the characteristics of candied paladang and determining the concentration of adding the carrot puree to produce the best characteristics of candied paladang. The research based on a Completely randomized design (CRD) with the addition of carrot puree concentration treatment with 6 levels: 0%; 5%; 10%; 15%; 20% and 25%. Each treatment was replicated 3 times to obtain 18 experimental units. Data was analyzed using analysis of variance and if treatment had a significant effect, its followed by the Duncan multiple range test (DMRT). The results showed that the addition ofcarrot puree had a significant effect (P<0.05) to the moisture content, ?-carotene content, ?-carotene bleaching, value of L*, a*, b*, colour (hedonic and scoring), flavour (hedonic), texture (hedonic and scoring), taste (hedonic)and overall acceptance. The addition of 25% carrot puree for producing candied paladang the best characteristics with moisture content 32.21%, ?-carotene content 3.36% mg/100g, ?-carotene bleaching 0.09 mg/ml, value of L* 30.74, value of a* 22.23, value of b* 25.58. Colour reddish orange and liked, flavour is normal, very soft texture and normal, taste is normal, and overall acceptance is normal.